Star trek. Volume 5 - Johnson, Mike (Comic book author); Johnson, F. Leonard (Frank Leonard), 1945-; Parrott, Ryan (Diamond Comic Distributors, 2013)
Features the back stories of Enterprise crew members McCoy, Uhura, Scotty, Chekov, and Sulu.